PERILAKU DALAM PENGELOLAAN SAMPAH DAN KONDISI LAYANAN PENGELOLAAN SAMPAH KOTA MALINAU - Nuzula Elfa Rahman (JURNAL AGRIMENT, 2017)
This research was aimed to investigate household practices of waste management in Malinau Regency, and local perception toward municipality waste management service. The results show that, in term of practices, the citizens has been aware on the importance of sanitation, although the implementation still needs improvement. Most respondents claimed that they don’t litter, yet it is visibly shown by the state of the rivers, in which floating pile of waste could be easily found. Littering is also common in public facilities such as market. Citizens of Kota Malinau also hasn’t yet established comunal/collective waste management. On positive note, citizens has already practiced solid waste sorting and reusing for animal feeding purpose. Apparently it is common in Malinau to utilize leftover food and kitchen waste for feeding livestock animals. In addition, schools in Malinau has pionereed in establishing organized waste management. In regard of municipality waste management, the citizens’ concern is more emphasized on the insufficient number of proper public waste bins and the ineffectiveness of collecting schedule from municipality. As part of waste management development in Kota Malinau, municipality needs to be actively educate people, since in waste management that complies with 3R (Reduce, Reuse, and Recycle) principle, households are required to perform proper waste sorting.